Treatment outcomes of extensive drug resistant tuberculosis in the penitentiary system of the Russian Federation - S. A. Sterlikov; L. I. Rusаkovа; S. B. Ponomаrev; V. B. Gаlkin; V. S. Burykhin (Туберкулез и болезни лёгких)
Despite the growing level of tuberculosis cases with extensive drug resistance and failing treatment of such patients, treatment outcomes of extensive drug resistant tuberculosis in the penitentiary system have never been studied. The objective of the study is to investigate treatment outcomes of extensive drug resistant tuberculosis in the penitentiary system of the Russian Federation. It was observed that treatment success of extensive drug resistant tuberculosis was poor (21.4%), which was first of all due to treatment failures (34.5%) and patients transferred out (27.7%). Relatively low mortality (6.0%) was typical of treatment outcomes. In order to enhance treatment effectiveness of extensive drug resistant tuberculosis in the penitentiary system of the Russian Federation, it would be reasonable to expand quality laboratory diagnostics and use of collapse therapy and to introduce the Federal Register of TB cases.